Sobrevida e morbimortalidade de pacientes submetidos à laparotomia exploradora com intenção de tratar carcinomatose peritoneal com operação de citorredução e quimioterapia intraperitoneal - Bernardo Hanan (2013)
Background: Peritoneal metastases are a common presentation in patients with some types of intra-abdominal cancers. Dr. PH Sugarbaker challenged the paradigm and considered peritoneal carcinomatosis (PC) to be a locoregional stage of the disease. Currently, the efficacy of combined treatment with cytoreductive surgery (CRS) and intraperitoneal chemotherapy (IPC) for PC arising from colorectal cancer (CRC), pseudomyxoma peritonei (PMP) and mesothelioma (MST) is an established in the oncologic literature. Although CRS and IPC are associated with high morbidity and mortality rates, survival improvement in selected patients with PC has been reported. Objective: The data were obtained from 73 patients affected with PC arising from CRC (38/52.1%), PMP (41.1%) or MST (6.8%) between 2002 and 2011. We reported the morbidity grade (II, III and IV), mortality and survival rates of the candidates after CRS and IPC from a single university institution in Brazil. Results: Forty-one (56.2%) women participated in this study, and the median age was 50 years (range 20-80). Thirty-nine patients (53.4%) underwent complete CRS and IPC, eighteen (24.7%) had a palliative procedure, and 16 (21,9%) had an open-and-close surgery. All of the patients who underwent a complete cytoreduction received IPC with mitomycin C, from which only 16/39 (41%) had hyperthermic IPC (39-41ºC). The median operative time was 360 minutes (range 60-840), and the median peritoneal cancer index (PCI) was 25 (range 3-39). Twenty-one patients (28.8%) required a blood transfusion. The overall morbidity rate was 23.3% in all of the procedures, and the grade II and III/IV complication rates were 11% and 12.3%, respectively. The most frequent complication was the formation of an anastomotic fistula (4.4%). There were no complications in the open-and-close group. The overall mortality rate was 5.5%. The univariate analysis showed that CRS and IPC (p=.029), a blood transfusion (p=.002) and the operative time (p=.001) were significant factors for the occurrence of postoperative complications. Patients with PC from CRC who underwent complete CRS and IPC had overall survival rates of 81.3%, 12.5% and 12.5% at 1, 3 and 5 years, respectively. In contrast, patients with PC from CRS who had incomplete cytoreduction had overall survival rates of 45%, 0% and 0% at 1, 3 and 5 years, respectively. Patients with PC from PMP who underwent complete CRS and IPC had overall survival rates of 84.2%, 77.7% and 77.7% at 1, 3 and 5 years. In contrast, patients with PC from PMP who had incomplete cytoreduction had overall survival rates of 72.7%, 39% and 0%, respectively. Conclusion: CRS and IPC, when possible, increase the survival rates of patients with PC arising from CRC and PMP. The survival gains were obtained despite high, but acceptable morbidity and mortality rates. These findings are comparable to those of previous reports.